2021
DOI: 10.1002/adtp.202100016
|View full text |Cite
|
Sign up to set email alerts
|

Europium Hydroxide Nanorods Mitigate Hind Limb Ischemia in Wistar Rats

Abstract: Lack of adequate blood supply to the limb extremities results in critical limb ischemia (CLI) and subsequent tissue death. Conventional approaches for CLI treatment include bypass surgery and angioplasty, which achieved limited clinical success due to their complex invasiveness. Of late, growth factor and cell‐based therapies emerged as alternative treatment strategies for CLI. However, these strategies could not achieve much success due to the associated drawbacks. Earlier, this study group develops europium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…Sighting Study (Single-Dose Study): The sighting study was performed for selecting appropriate dose for the main study along with determination of maximum tolerable dose (MTD). [27,107] The sighting study or singledose toxicity study was performed in female C57BL/6J mice (n = 2) by intraperitoneal administration (I.P.) of CMnNP.…”
Section: Supporting Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…Sighting Study (Single-Dose Study): The sighting study was performed for selecting appropriate dose for the main study along with determination of maximum tolerable dose (MTD). [27,107] The sighting study or singledose toxicity study was performed in female C57BL/6J mice (n = 2) by intraperitoneal administration (I.P.) of CMnNP.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Limb Ischemia: Unilateral hindlimb ischemic prototype was established in female mice (BALB/c) through femoral artery ligation as per published report. [27,51] For developing a model of hindlimb ischemia, initially the animals were anesthetized with I.P. administration of ketamine plus xylazine cocktail injection.…”
Section: Supporting Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, the current research presents a novel nanomedicine method utilizing ZONFs for PAD treatment. Recent research has demonstrated that nanorods made of europium hydroxide can promote therapeutic angiogenesis, which in turn helps reduce the vascular toxicity caused by cadmium exposure [ 188 ]. This effect is seen in Wistar rats who have had myocardial ischemia.…”
Section: Peripheral Vascular Disease (Pvd)mentioning
confidence: 99%